Glia as antigen-presenting cells in the central nervous system. (December 2022) - Sutter, Pearl A.; Crocker, Stephen J.
Abstract: The contribution of the cells within the central nervous system (CNS) toward adaptive immune responses is emerging and incompletely understood. Recent findings indicate important functional interactions between T-cells and glial cells within the CNS that may contribute to disease and neuropathology through antigen presentation. Although glia are not classically considered antigen-presenting cell (APC) types, there is growing evidence indicating that glial antigen presentation plays an important role in several neurological diseases. This review discusses these findings which incriminate microglia, astrocytes, and oligodendrocyte lineage cells as CNS-resident APC types with implications for understanding disease.